(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Disability is a global health concern and there is no exceptional in Pakistan for disable people. So, being a physical therapist assessment of physical therapies attitude towards disable people is important for which reason we considered Attitude Toward Disabled Persons (ATDP) scale it is based on agreement and disagreement questionnaire from physical therapists of Faisalabad. Objective: The current study objective was to investigate the level of attitude toward disabled person among physical therapists. Methods: This cross-sectional survey-based study was conducted to examined the attitude of physical therapists towards disabilities using ATDP scale consisting of 20 items based on scoring (+3+2+1-1-2-3) and data was collected from 50 physical therapists of different organization private hospitals, public sectors and physical therapy clinics of Faisalabad. Statistically analysis was done by using SPSS version 23. Results: From Population of 50 physiotherapists 25.11% of physiotherapists scored agree very much (+3), 20.12% of them scored agree pretty much (+2), 22.33% of them scored agree to Little (+1), 15.92% of them scored disagree a little (-1), 6.5% of them scored disagree pretty much (-2)’ 10% off them scored disagree very much (-3). Hence positive attitude is higher than negative attitude. Physical therapists overall have more positive attitude on ATDP questionnaire consist of 20 questions based on attitude options (agree considered positive attitude and disagree considered negative attitude) according to questions the more positive attitude was toward person with disability the more likely they are to be comfortable with challenging rehabilitation. Chi square test shows a significant result of positive attitude of physiotherapist towards disability. Conclusion: The study conclude that physical therapists hold moderately positive attitude towards disabled persons and perceived disabled persons as quite similar to non-disabled persons.